2019
DOI: 10.1016/j.landurbplan.2019.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Top-down segregated policies undermine the maintenance of traditional wooded landscapes: Evidence from oaks at the European Union’s eastern border

Abstract: Semi-open oak woods and solitary oaks commonly dominate the wooded fabric (i.e. the 'oakscape') of European traditional rural agricultural landscapes based on animal husbandry. However, modern land use systems fail to perpetuate oakscapes, posing a serious threat to biodiversity conservation and the associated diversity of ecosystem services. Reconstructing the dynamics of oakscape remnants can provide valuable insights concerning the maintenance of oakscapes. We used the socioeconomic transitions at the Europ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 45 publications
3
25
0
Order By: Relevance
“…Rather multiple fires have been more successful (Dey & Hartman, ; Hutchinson et al, ). This corresponds to Ziobro et al () and Bobiec et al (), who reported that reoccurring grass burning promoted Q. robur regeneration by reducing competing shade‐tolerant species in Ukrainian woodlands. We, therefore, suggest that additional experiments involving multiple burning events are needed to determine whether reoccurring fire provides Q. robur and Q. petraea competitive advantage.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Rather multiple fires have been more successful (Dey & Hartman, ; Hutchinson et al, ). This corresponds to Ziobro et al () and Bobiec et al (), who reported that reoccurring grass burning promoted Q. robur regeneration by reducing competing shade‐tolerant species in Ukrainian woodlands. We, therefore, suggest that additional experiments involving multiple burning events are needed to determine whether reoccurring fire provides Q. robur and Q. petraea competitive advantage.…”
Section: Discussionsupporting
confidence: 83%
“…Rather multiple fires have been more successful (Dey & Hartman, 2005;Hutchinson et al, 2012). This corresponds to Ziobro et al (2016) and Bobiec et al (2019) (Brose et al, 2014). Though burning was conducted at the very end of the growing season in this study, it is likely that the timing of the burns we applied impacted plants that were physiologically active.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations